Leukocytoclastic vasculitis after long-term treatment with sunitinib: A case report - Karadimou, A.; Migou, M.; Economidi, A.; Stratigos, A.; Kittas, C.; Dimopoulos, M.A.; Bamias, A. (Case Reports in Oncology, 2011)
We report on a 63-year-old woman, previously in good health, who had undergone nephrectomy for clear cell renal cell carcinoma in 2002. Because of systemic relapse with multiple lung metastases in 2006, the patient was treated with sunitinib 50 mg daily on a 4-weeks on-/2-weeks off-schedule. After 3 years of treatment, she developed a purpuric rash on her feet and trunk. Biopsy revealed leukocytoclastic vasculitis. No other organ involvement was diagnosed. She was started on oral prednisone 30 mg daily with rapid resolution of the vasculitic skin lesions. Sunitinib was temporally discontinued and reintroduced at the same dose level. Reappearance of a less serious vasculitis after 2 cycles of re-treatment was resolved in the weeks off-treatment and by reducing the dose of sunitinib along with 5 mg of prednisone daily. One year after the diagnosis, the patient is still on this therapy. Oncology providers should be aware of this rare but potentially serious, possible adverse effect of sunitinib. Copyright © 2011 S. Karger AG, Basel.
Keywords: Leukocytoclastic vasculitis; Renal cell cancer; Sunitinib